2017
DOI: 10.1016/j.ijchp.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based interventions for the treatment of depressive rumination: Systematic review and meta-analysis

Abstract: Background/Objective: This systematic review aims to evaluate the effect of interventions based on the mindfulness and/or acceptance process on ruminative thoughts, in patients with depression. Method: Electronic searches in Medline, Embase, Cochrane Central, PsycInfo, and Cinahl until December 2016, in addition to hand-searches of relevant studies, identified eleven studies that fulfilling inclusion criteria. Results: A meta-analysis of the effect of the intervention compared to usual care showed a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 48 publications
6
61
0
1
Order By: Relevance
“… 11 More recently, Perestelo-Perez et al conducted a systematic review and meta-analysis in 2017 to evaluate the effect of mindfulness-based interventions on ruminative thoughts in individuals with current or past depressive disorders. 10 Results of 11 studies showed that MBCT compared to usual care produced a significant reduction in rumination, independent of the number of past depressive episodes.…”
Section: Efficacy Of Mbct For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 More recently, Perestelo-Perez et al conducted a systematic review and meta-analysis in 2017 to evaluate the effect of mindfulness-based interventions on ruminative thoughts in individuals with current or past depressive disorders. 10 Results of 11 studies showed that MBCT compared to usual care produced a significant reduction in rumination, independent of the number of past depressive episodes.…”
Section: Efficacy Of Mbct For Depressionmentioning
confidence: 99%
“…A more recent meta-analysis conducted by Perestelo-Perez et al compared the effect of MBCT to ACCs on rumination for individuals with a depressive disorder. 10 Using three studies, results indicated that MBCT appeared as effective at reducing rumination as other treatments such as medication, CBT, and behavioral activation. However, authors recommended caution when interpreting these results given the low number of studies included.…”
Section: Efficacy Of Mbct For Depressionmentioning
confidence: 99%
“…In addition, MBCT was found as effective (but not more effective) at reducing rumination as other active treatments (e.g. medication, cognitive-behavioral therapy, and behavioral activation) [47].…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Shallcross et al compared MBCT with ACCs in 2015, the results were found that MBCT did not differ from the ACCs on rate of depression relapse, symptom reduction, and life satisfaction [49]. A recent meta-analysis indicated that MBCT was more effective in reducing rumination with a depressive disorder than ACCs [50]. The inconsistencies between these studied were probably owing to small sample size, poor quality of methodology and lack of long-term follow-up.…”
Section: Comparison With Other Viewsmentioning
confidence: 99%